Corporate Liability In Child Rights Violations - Ahmad Sofian Sofian; Batara Mulia Hasibuan; Anisa Oktavia Perwita Sari; Mark P. Capaldi (Universitas Muhammadiyah Purwokerto, 2025)
This paper aims to explore the liability of the business sector in violations of children's rights that occur in Indonesia. In exploring the issue of liability, the author integrates the case with the principle of rights in business that applies globally known as Children's Rights and Business Principles (CRBP). Then the problem raised in this research is how the attribution of responsibility of the business sector when running its business violates children's rights, how the business sector integrates CRBP in its business to prevent violations of children's rights. This research is a normative research and the legal materials used are Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection and Law No. 13 of 2003 concerning Labor. The findings of the research are that national laws do not specifically regulate the liability of the business sector when it violates children's rights. The business sector can only be held accountable in criminal or civil cases that cause harm to children. Therefore, this study recommends that CRBPs be integrated in the revision of the Child Protection Law and apply liability in the form of criminal or civil or administrative witnesses when violations of children's rights by the business sector occur.